2022
DOI: 10.3390/life12020262
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Exercise Training Remotely

Abstract: There has been increased incentivization to develop remote exercise training programs for those living with chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD). Remote programs offer patients an opportunity to overcome barriers to accessing traditional in-person programs, such as pulmonary rehabilitation (PR). Methods to deliver exercise training remotely range in complexity and types of technological modalities, including phone calls, real-time video conferencing, web- and app-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…There was a significant improvement in the 30-second STS score (p=0.000) between baseline and post-training (Figure 2). The average increase was 8.32 3.95 (SD) reps (range [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The difference in both the STS and 6MWD performance score between baseline and post-training were calculated and were found to be positively correlated (r =0.75).…”
Section: Secondary Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…There was a significant improvement in the 30-second STS score (p=0.000) between baseline and post-training (Figure 2). The average increase was 8.32 3.95 (SD) reps (range [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The difference in both the STS and 6MWD performance score between baseline and post-training were calculated and were found to be positively correlated (r =0.75).…”
Section: Secondary Outcomesmentioning
confidence: 96%
“…The use of telehealth in conjunction with wearable technology, and evidence-based behavioural change techniques, provides a low-cost and scalable solution to exercise training promotion in PH, that is likely to be sustainable and foster long-term behaviour change. Research of remote programmes in other chronic respiratory diseases appears to be largely beneficial in improving clinical outcomes [ 15 ]. To our knowledge, no previous research has examined the feasibility and effectiveness of a home-based physical activity intervention that is delivered entirely remotely in PH patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital technologies offer the potential to overcome barriers to accessing PR services (such as travel, transport and location), by increasing coverage in more isolated areas and enabling closer monitoring of patients [1,25]. However, they may also aggravate the existing access disparities, due to the need of digital technology and appropriate infrastructures, including internet access [7,94]. Recent studies have found that, while digital technologies are ubiquitous in daily lives of most patients with CRDs, particularly mobile phones [95][96][97], only a limited number of patients have access to the internet and/or are confident in using it [95][96][97][98], which may create a problem of inequitable access to intervention enrolment.…”
Section: A Technology and Internet Accessmentioning
confidence: 99%
“…However, it is acknowledged that digital interventions are not a "one size fits all" approach [25], and there is a need to better understand the characteristics of patients who can benefit most from digital health. Digital home-based programmes may be more suitable for patients with good connectivity and digital self-efficacy, while centre-based programmes may be a better alternative for those who lack the resources or are uncomfortable using technology [94]. The assessment of patients' suitability for digitally enabled interventions may be facilitated by the use of tools such as the 8-item Dutch Blended Physiotherapy Checklist [101].…”
Section: A Technology and Internet Accessmentioning
confidence: 99%